Copper phthalocyanine complex as electrocatalyst for hydrogen evolution reaction - KOCA, ATIF (ELSEVIER SCIENCE INC, 2009)
In this work, we have sought economically viable methods for hydrogen evolution reaction (her). For this purpose, we have investigated the voltammetric and in situ spectroelectrochemical behavior of copper phthalocyanine complex and its electrocatalytic activity for her. In spite of the belief that the complexes bearing redox active metal center can catalyze hydrogen evolution reactions, copper phthalocyanine having ring-based redox processes shows excellent electrocatalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Copper phthalocyanine; Hydrogen evolution reaction; Electrocatalyst; SPECTROELECTROCHEMICAL CHARACTERIZATION; REDUCTION; COBALT